Kognition tutkiminen iäkkäiden ajokykyarviossa - Kuikka, Pekka; Akila, Ritva; Nybo, Taina; Ranta, Mervi (Psykologia : tiedepoliittinen aikakauslehti, 2006)
Assessing cognition among elderly drivers.
Keywords: ajokyky; muisti (kognitio); havainnointi; liikennepsykologia; kognitio; tarkkaavaisuus; terveydentila; kognitiiviset prosessit; neuropsykologia; häiriöt; aivot; testit; ikääntyminen; arviointi; ikääntyneet; körförmåga; minnet (kognition); observerande; trafikpsykologi; kognition; uppmärksamhet; hälsotillstånd; kognitiva processer; neuropsykologi; störningar; hjärna; test; åldrande; utvärdering; äldre